Electroacupuncture for Irritable Bowel Syndrome: A Review of Randomized Controlled Trials - So Rim Kim; Ga Yeong Yi; Yeji Lee; Jin Hyun Kim; Minjo Seo; Dawon Lee; Minji Sun; YeonSun Lee (Journal of Acupuncture Research)
This review aimed to explore the therapeutic effects of electroacupuncture (EA) on irritable bowel syndrome (IBS), a commonly diagnosed functional gastrointestinal disorder, through an analysis of randomized controlled trials (RCTs). The RCTs were collected from PubMed, the Cochrane Library, Embase, China National Knowledge Infrastructure, and Research Information Service System. Altogether, seven studies were selected. The analysis revealed that EA significantly affected various IBS evaluation indicators, including the Bristol Stool Form Scale, 36-Item Shortform Survey, Hamilton Depression Rating Scale, Hamilton Anxiety Rating Scale, Self-rating Depression Scale, Self-rating Anxiety Scale, and Visual Analogue Scale. Notably, EA showed promising results for treating IBS—constipation predominant (IBS-C). However, the number of RCTs on IBS, particularly IBS-C, is limited, and the underlying mechanisms of IBS remain unclear. Therefore, further high-quality RCTs and studies are warranted to elucidate the therapeutic effects of EA according to the pathophysiology of IBS.